Monetisasi Youtube Perspektif Tafsir Maqashidi - Alfi Nur'aini (Jurnal Penelitian Agama, 2021)
The presence of youtube as today's most popular social media is a consequence of the inexorable advance of technology and science. Youtube's popularity has also been an effect of the covid19 pandemic that requires humans to adapt to avoiding crowds. Amid the covid19 pandemic that created the struggle for revenue, youtube is being used as a medium for generating revenue. Anyone can make a youtube channel and become a youtuber. A youtube channel can earn money from the content it generates through the monetizing process. Youtube monetary is one of the best solutions to staying incomes and staying clear of crowds by health protocol. The practice of youtube monetizing has become a new and also a new profession today. The study discussed youtube monetary with a maqashidi interpretation perspective. The method in this study is qualitative or library research with the maqashidi interpretation approach. The conclusion of this study is: first, monetary on youtube becomes a new way of earning money. Youtube monetary is permitted so long as it has greater valuation than its youth. Second, youtube monetary can serve as a means of safeguarding the soul (hifdz al-nafs) and productive preservation of wealth (hifdz al-mal).